2004
DOI: 10.1021/bi035923w
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Mechanism of Quinone Oxidoreductase 2 and Its Inhibition by the Antimalarial Quinolines

Abstract: Quinone oxidoreductase 2 (QR2) purified from human red blood cells was recently shown to be a potential target of the quinoline antimalarial compounds [Graves et al., (2002) Mol. Pharmacol. 62, 1364]. QR2 catalyzes the two-electron reduction of menadione via the oxidation of N-alkylated or N-ribosylated nicotinamides. To investigate the mechanism and consequences of inhibition of QR2 by the quinolines further, we have used steady-state and transient-state kinetics to define the mechanism of QR2. Importantly, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 29 publications
8
122
0
2
Order By: Relevance
“…However, the protein cannot refold into the active form in the absence of any metal ions in the refolding buffer. Consistent with our studies, Kwiek et al recently reported that the QR2 enzyme purified from human redblood cells contained partially zinc and partially copper ions (45).…”
Section: Implication Of the Catalytic Mechanismsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the protein cannot refold into the active form in the absence of any metal ions in the refolding buffer. Consistent with our studies, Kwiek et al recently reported that the QR2 enzyme purified from human redblood cells contained partially zinc and partially copper ions (45).…”
Section: Implication Of the Catalytic Mechanismsupporting
confidence: 93%
“…The catalytic mechanism of QR2 and QR1 is likely very similar, a classic ping-pong mechanism (45). FAD is reduced by accepting a hydride from the reduced nicotinamide to form the FADH 2 -enzyme complex, and subsequently, nicotinamide is released from the active site.…”
Section: Implication Of the Catalytic Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic studies show that PQ and CQ both inhibit NQO2 in the micromolar range, with K I values of 1.0 and 0.6 M, respectively (25), but PQ exhibits competitive inhibition against the reducing co-factor (NRH), whereas CQ competes with the quinone substrate. This pattern of inhibition can be explained by the ping-pong kinetic mechanism that NQO2 uses.…”
mentioning
confidence: 99%
“…QR2 has a role in the detoxification processes of quinones, specifically the two-electron reduction of menadione by the oxidation of N-alkylated or N-ribosylated nicotinamides (34). Knock-out models of QR2 in mice result in an increased susceptibility to polycyclic aromatic hydrocarbon-induced skin carcinogenesis, whereas inhibition of QR2 using quinacrine resulted in death of malaria-infected red blood cells by altering the redox status of the cell (33,35). Recently a role for QR2 in the tumor necrosis factor apoptotic signaling pathway has emerged in which QR2-deficient keratinocytes were shown to have suppressed survival signals and increased tumor necrosis factorinduced apoptosis (36).…”
Section: Discussionmentioning
confidence: 99%